QOBIZ SAZ ÁSPABI HAQQINDA AŃIZ ÁPSANALAR - Ayapov, S.B. (SCIENCE and SOCIETY, 2023)
This article talks about the art of karakalpak pawning, qobuz, a musical instrument of pawns, its making and legends. In addition, detailed information is given about the opinions of scientists about Qorqit father and Qobuz and the sources recorded by researchers from the mouths of the people.